Effectiveness of Mesenchymal Stem Cells in Tissue Regeneration in Ear Injuries: A Meta-Analysis - Hidayat, Rachmat (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Ear injuries are a common health problem and can cause significant hearing loss. Tissue regeneration in injured ears is still a big challenge. Mesenchymal stem cells (MSCs) have shown potential for tissue regeneration in various organs, including the ear. This meta-analysis aims to evaluate the effectiveness of MSCs in tissue regeneration in ear injuries. Methods: We conducted a literature search in various electronic databases, including PubMed, Cochrane Library, and Scopus, for studies examining the use of MSCs in tissue regeneration in ear injuries. Inclusion criteria included randomized controlled studies, prospective observational studies, and cohort studies examining the effectiveness of MSCs on hearing improvement, regeneration of ear structures, and reduction of inflammation. Results: A total of 12 studies with a total of 342 participants met the inclusion criteria. The meta-analysis results showed that MSCs significantly improved hearing improvement (standardized mean difference [SMD] = 0.67, 95% confidence interval [CI] 0.42-0.92, p < 0.001) and ear structure regeneration (SMD = 0.53, 95% CI 0.28 -0.78, p < 0.001). MSCs also showed effectiveness in reducing inflammation (SMD = -0.48, 95% CI -0.73-0.23, p < 0.001). Conclusion: MSCs are an effective and safe therapy for tissue regeneration in ear injuries. Further research is needed to optimize treatment protocols and evaluate the long-term effectiveness of MSCs.